Short and long term histopathologic effects of a polypropylene prosthesis on canine tracheas - Kılıç, Ş.; Özercan, İ. H. (My University, 2000)
In this study, it was aimed to investigate the pathological effects of a polypropylene prosthesis on the canine tracheas. Here, 6 control and 12 experimental group dogs were used. Experimental group dogs were divided equally into spiral group and ring groups according to the shapes of the prostheses used. Additionally, all dogs were allocated postoperatively to short term subgroup (SSG) (10 days) and long term subgroup (LSG) (Smonths) to determine the differentiation of pathological changes in time. Following euthanasia, the cervical tracheas of these dogs were removed affld from each trachea! segment four transversal section^ were prepared. Later, they were examined regarding to the complications such as inflammation, degeneration and necrosis. It was determined that the degrees of these complications varied from mild to severe and their mean values were higher in ring and spiral groups than control group. In addition, the severity of these complications in experimental group dogs non-significantly reduced (p>0.05) in PSG as compared to SSG. Although these complications appeared to persist, they were not progressive and caused no respiratory distress. Histopathologically, no significant difference was also found between the different shapes of polypropylene prostheses. These results show that polypropylene prosthesis can be a useful material for reconstructing the canine trachéal collapse. Key Words: Dog, Polypropylene Prosthesis, Trachea, Pathology. _2ÖZET Bu çalışmada, bir polipropilen protezin köpek trakeası üzerine olan patolojik etkilerinin incelenmesi amaç- landı. Burada 6 kontrol ve 12 deney grubu köpek kullanıldı. Deney grubu köpekler protezlerin şekline göre spiral ve ring gruplarına eşit olarak ayrıldılar. Ayrıca, patolojik değişikliklerde zamanla oluşan farklılıkları incelemek için deney ve kontrol grubu köpekler postoperatif olarak kısa (10 günlük) ve uzun süreli (3 aylık) alt gruplara ayrıldılar. Ötenaziden sonra köpeklerin servikal trakeaları alındı ve her bir segmentten dört transversal kesit hazırlandı. Bunlar yangı, dejenerasyon ve nekroz gibi komplikasyonlar yönünden incelendi. Bu kompikasyonların derecelerinin hafiften şiddetliye kadar değiştiği ve ortalama değerlerinin kontrol grubuna göre spiral ve ring gruplarında daha yüksek olduğu saptandı. Kısa ve uzun süreli deney grupları karşılaştırıldığından bozuklukların şiddetinde azalmanın olduğu ancak bu azalmanın istatistiksel yönde önemli olmadığı gözlendi. Sonuç olarak, bu bozuklukların bazı vakalarda uzun süreli olmasına karşın ilerleyici bir seyir göstermedikleri ve her hangi bir solunum problemine neden olmadıkları saptandı. Değişik şekillerdeki polipropilen protezler arasında histopatolojik olarak dikkate değer bir fark gözlenmedi. Bu bulgulardan bir polipropilen protezin köpek trakeal kolapsının rekonstrüksiyonunda kulla-nılması için yararlı bir materyal olduğu kanısına varıldı.
Keywords: Nefes borusu; histopatoloji; cerrahi; patoloji; köpek; ameliyat sonrası komplikasyonlar; protezler; polipropilen